Pulmonary mucormycosis presenting with vocal cord paralysis - Gayathri Devi, H.J. (Elsevier, 2013)
Pulmonary mucormycosis is a relatively uncommon infection. It can present in various forms. Very few cases of pulmonary mucormycosis presenting as vocal cord paralysis have been described in the literature. We report a case of pulmonary mucormycosis presenting as vocal cord paralysis in an uncontrolled diabetic patient.